Problem-based learning approach to improve service skills of badminton in physical education learning - Rusfan Dinata Prabandaru; Lismadiana Lismadiana; Fitri Agung Nanda (International Journal of Education and Learning, 2020)
Problem-based learning is a method used to solve a problem in learning. This study aimed to determine whether learning badminton service skills by applying a problem-based learning approach can improve badminton service hit skills. The research method uses the classroom action research (CAR) method by interpreting the data and comparing each cycle's results with a percentage approach to measure the achievements of the actions taken. The results obtained from the data taken before the action were 23.68% of students who mastered basic movement skills hitting badminton service. After the first cycle, 34.21% of the students mastered the material, and, at the end of the second cycle, 52.63% of the students mastered the basic movement skills of hitting badminton service. From the preliminary data, there was a significant increase in cycle I and cycle II, the conclusion is that there increased the skill of hitting badminton service through the problem based learning approach (PBL) in students of third-grade of Pagergunung elementary school 1 in 2018/2019. Increased mastery of hitting service skills badminton, which was improved through applying the problem-based approach, was 28.94%.